ASSESSMENT OF LONG-TERM OUTCOMES OF PATIENTS UNDERGOING PERCUTANEOUS CORONARY INTERVENTION (PCI) FOR CHRONIC TOTAL OCCLUSIONS - ASLAM, K; IQBAL, E; KHAN, MS; KHAN, FR; SAJJAD, W (Biological and Clinical Sciences Research Journal, 2024)
A minimal surgical procedure called ‘PCI’ (percutaneous coronary intervention) is performed to treat those who have diseases of the coronary arteries. A period of more than three months of entire blockage of a coronary artery results in a ‘CTO’ (chronic total occlusions). The primary goal of the research is to determine the performance of patients who have ‘PCI’ (percutaneous coronary intervention) for chronic total occlusions (CTO). The study was conducted at Lady Reading Hospital MTI from March 2022 to December 2022. The research included 400 individuals with ‘percutaneous coronary intervention’ for ‘CTO.’ Information was gathered via follow-up appointments and records from patients. All-caused death was the study's primary objective; major adverse cardiac events (MACE), repeated revascularization’, and standard of life were its additional objectives. Survival analysis and descriptive statistical methods were used to analyze the data. This research looked at the long-term results of individuals who had ‘percutaneous coronary intervention ‘for ‘A CTO’ and revealed that 400 individuals had at least one ‘percutaneous coronary intervention ‘for a ‘CTO.’ The individual's average age was 58.9 ± 6.07 years, and 70.3% of them were men. This research concludes that with a total success rate of 87.5%, ‘percutaneous coronary intervention ‘for chronic complete occlusions may result in favorable long-lasting results.